2020
DOI: 10.1108/ijccsm-10-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

Household resilience to climate change hazards in Uganda

Abstract: Purpose As climate change shocks and stresses increasingly affect urban areas in developing countries, resilience is imperative for the purposes of preparation, recovery and adaptation. This study aims to investigate demographic characteristics and social networks that influence the household capacity to prepare, recover and adapt when faced with prolonged droughts or erratic rainfall events in Mbale municipality in Eastern Uganda. Design/methodology/approach A cross-sectional research design was used to eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
(41 reference statements)
1
11
1
Order By: Relevance
“…Findings of our study corroborate those reported by the National Capacity Needs Assessment (MECNT and UNDP, 2009) and Chinedum et al (2015) in DRC. They match those found by Chia et al (2016) in Cameroon, Onyeneke et al (2017) in Nigeria, Saalu et al (2020) in Kenya and Oriangi et al (2020) in Uganda.…”
Section: Discussionsupporting
confidence: 90%
“…Findings of our study corroborate those reported by the National Capacity Needs Assessment (MECNT and UNDP, 2009) and Chinedum et al (2015) in DRC. They match those found by Chia et al (2016) in Cameroon, Onyeneke et al (2017) in Nigeria, Saalu et al (2020) in Kenya and Oriangi et al (2020) in Uganda.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the three divisions in the municipality (Figure 2), results revealed that, Industrial division has the highest average resilience score (1.7), followed by Northern division (0.9) and Wanale division (−1.9). The relatively higher resilience score by Industrial division contradicts findings of the previous study in the municipality that focused on only the social dimension and reported that Industrial division was the least resilient [50].…”
Section: The Average Resilience Scores Of the Three Division In Mbalecontrasting
confidence: 99%
“…Other notable impacts documented in the literature include rising lake water levels (Mugyenyi et al, 2020), torrential downpours causing floods in cities and towns, and rising temperatures (Klara & Hajdu, 2017; Oriangi et al, 2020; Tenywa et al, 2017; Nagasha et al, 2019). While being on the receiving end of the effects of climate change presents young people as one of the groups of individuals who have fallen victim to human-driven environmental changes, their response to local, national, and global efforts to mitigate its effect on society could well make them part of the solution.…”
Section: Methodsmentioning
confidence: 99%
“…While being on the receiving end of the effects of climate change presents young people as one of the groups of individuals who have fallen victim to human-driven environmental changes, their response to local, national, and global efforts to mitigate its effect on society could well make them part of the solution. Overall the literature review presents young people as “victims and solution providers” in the climate change and development equation (Osuret, et al, 2016; Oriangi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation